Targeting Glutathione S-transferase M4 in Ewing sarcoma - Zhuo, Rupeng; Kosak, Kenneth M.; Sankar, Savita; Wiles, Elizabeth T.; Sun, Ying; Zhang, Jianxing; Ayello, Janet; Prestwich, Glenn D.; Shami, Paul J.; Cairo, Mitchell S.; Lessnick, Stephen L.; Luo, Wen (Frontiers in Pediatrics, 2014)
Ewing sarcoma is a malignant pediatric bone and soft tissue tumor. Although the 5-year survival rate of localized disease approaches 75%, the prognosis of metastatic and/or therapy-resistant disease remains dismal despite the wide use of aggressive therapeutic strategies. We previously reported that high expression of glutathione S-transferase M4 (GSTM4) in primary tumors correlates with poor patient outcomes. GSTM4 is required for oncogenic transformation and mediates resistance to chemotherapeutic drugs in Ewing sarcoma cells. Here, we performed RNA-sequencing analyses of Ewing sarcoma cells and combined our results with publicly-available datasets to demonstrate that GSTM4 is a major GST specifically expressed in Ewing sarcoma. Pharmacological inhibition of GSTM4 activity using a pan GST inhibitor, 6-(7-nitro-2,1,3-benzoxadiazol-4-ylthio) hexanol (NBDHEX), significantly limited cellular proliferation and oncogenic transformation of Ewing sarcoma cells. Moreover, combined use of NBDHEX and etoposide synergistically increased cytotoxicity, suggesting a role for GSTM4 as an inhibitor of apoptosis. Mechanistic studies revealed that GSTM4 limits apoptosis owing to its ability to interact with Apoptosis Signal-regulating Kinase 1 (ASK1) and inhibit signaling via the c-Jun N-terminal Kinase axis. To exploit our observation that GSTM4 expression is specifically up-regulated in Ewing sarcoma, we tested the effect of a GSTM4-activated anti-cancer agent, O2-(2,4-dinitrophenyl) 1-[(4-ethoxycarbonyl)piperazin-1-yl]diazen-1-ium-1,2-diolate or JS-K, on tumor growth and survival. We found that JS-K robustly decreased Ewing sarcoma cell viability and xenograft tumor growth, and improved overall survival of xenograft mice. Our data suggest that GSTM4 is a novel therapeutic target for the treatment of high GSTM4-expressing Ewing sarcoma. Strategies that combine standard chemotherapy with agents that inhibit GSTM4, or that are activated by GSTM4, or that block GSTM4/ASK1 interaction